2023
DOI: 10.21203/rs.3.rs-2977859/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Lumbar Multifidus Characteristics in University Level Athletes May be Predictors of Low Back Pain and Lower Limb Injury

Abstract: Background Low back pain (LBP) is highly prevalent in athletes, with lumbar multifidus (LM) atrophy and increased LM cross-sectional area (CSA) reported in athletes with LBP. Decreased LM CSA and thickness have also been previously associated with lower limb injury (LLI) in athletes. Yet, previous research has only investigated connections between LM, LBP, and LLI in small samples of athletes in a single sport at a time. The current study aimed to (1) examine LM morphology and function across a general sample… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…While our study did not separate left and right sides to compare muscle morphology and composition, it would be interesting to see if the smaller side of the ES at L5 had any correlation with the smaller side in the LM and PS. Previous research suggested that LM CSA % asymmetry at L5 was the best predictor of lower limb injury in athletes [ 24 ]. With increased asymmetry of the LM, one may expect the ES to be smaller on the contralateral side as a means of compensation to aid in stabilization of the spine on the affected side.…”
Section: Discussionmentioning
confidence: 99%
“…While our study did not separate left and right sides to compare muscle morphology and composition, it would be interesting to see if the smaller side of the ES at L5 had any correlation with the smaller side in the LM and PS. Previous research suggested that LM CSA % asymmetry at L5 was the best predictor of lower limb injury in athletes [ 24 ]. With increased asymmetry of the LM, one may expect the ES to be smaller on the contralateral side as a means of compensation to aid in stabilization of the spine on the affected side.…”
Section: Discussionmentioning
confidence: 99%